GAYA BAHASA DAKWAH DI INSTAGRAM PADA KOMUNITAS PEMUDA HIJRAH - Hazna Fairuz Sabilla (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Abstract: This study aims to analyze the style of da’wah discourse on Instagram within the Shift Pemuda Hijrah Bandung community, specifically through the official account @pemuda_hijrah_org. The research background stems from the shift from traditional da’wah to digital da’wah, which better suits the characteristics of urban youth. The method used is a qualitative, interpretive approach grounded in netnography, involving intensive digital observation of the account’s activities in March and April 2026, with the Ramadan period serving as the primary unit of analysis. The research findings indicate that the language style of da’wah on Instagram is characterized by the use of popular vocabulary, slang, and persuasive-horizontal narratives that foster a sense of closeness with the audience. Additionally, integrating text with aesthetically pleasing visuals demonstrates efforts to strengthen engagement and foster a new, more inclusive religious identity relevant to digital popular culture. The study’s conclusion affirms that the success of the Shift Pemuda Hijrah community’s da’wah lies in the precision of its communicative accommodation strategies, which connect theological messages with the psychological and social needs of urban youth, thereby positioning da’wah within a contemporary creative lifestyle.